First description of the nest, eggs and cooperative breeding behavior in Sharpe’s Wren (Cinnycerthia olivascens): Primera descripción del nido, los huevos y comportamiento de cría cooperativa en el soterrey caferrojizo (Cinnycerthia olivascens) (Ornitología Colombiana, 2021)
We provide the first description of the nest, eggs and nestlings of Sharpe’s Wren (Cinnycerthia olivascens) from northeastern Ecuador, and we document the occurrence of cooperative breeding in this species. Cinnycerthia olivascens builds large, enclosed ball nests with a downward-projecting tubular entrance. The eggs are off-white with sparse reddish-brown speckling. We show that at least three adults may participate in nest-building and probably contribute to nestling provisioning. Our video observations document fledgling and show that the nestlings’ diet consisted of small invertebrates.